Pressure-sensitive adhesive for display and preparation method thereof

By using a single-component acrylate copolymer pressure-sensitive adhesive, the combination of soft monomers, hard monomers, crosslinked monomers and macromolecular monomers is improved, and the adhesion and aging resistance of the pressure-sensitive adhesive are solved. The stability and cost issues of pressure sensitive adhesives when used in liquid crystal displays in the prior art.

CN119410307APending Publication Date: 2025-02-11DEBANG (KUNSHAN) MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411737370.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

When used in liquid crystal displays, existing pressure-sensitive adhesives have problems such as insufficient adhesion, poor stickiness, and poor aging in high temperature and high humidity environments, resulting in unstable product quality and high production costs.

Method used

A single component acrylate copolymer pressure sensitive glue is used, and its raw materials include soft monomers, hard monomers, crosslinked monomers, macromonomers and initiators. The prepolymerization of components A and component B and The later crosslinking reaction improves the polydispersibility coefficient of weight average molecular weight and molecular weight distribution.

Benefits of technology

It improves the adhesion, viscosity and light transmittance of the pressure-sensitive adhesive, enhances its aging resistance in high temperature and high humidity environments, simplifies the process and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005161811350000051
    Figure BDA0005161811350000051
  • Figure BDA0005161811350000061
    Figure BDA0005161811350000061
  • Figure BDA0005161811350000081
    Figure BDA0005161811350000081
Patent Text Reader

Abstract

The invention relates to the technical field of pressure-sensitive adhesives, in particular to a pressure-sensitive adhesive for display and a preparation method thereof. The pressure-sensitive adhesive for display comprises an acrylate copolymer and a solvent, and the acrylate copolymer comprises the following raw materials in parts by weight: 100-150 parts of a soft monomer, 10-50 parts of a hard monomer, 1-10 parts of a crosslinking monomer, 1-10 parts of a macromonomer, 0.1-1 part of an initiator and 0-0.2 part of an auxiliary agent. The pressure-sensitive adhesive is a single component and can be directly used, and the process is simple and controllable; a curing agent does not need to be added in the later period, and the aging failure risk caused by curing agent batch difference and the post-crosslinking process is avoided; the molecular weight of the pressure-sensitive adhesive is greatly improved and the molecular weight distribution is controlled in a narrower range by using the macromonomer, and the prepared pressure-sensitive adhesive has excellent cohesiveness, high holding power, high light transmittance and aging resistance, meets the processing properties of warping resistance, cutting property and reworking property, and meets the use requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of pressure-sensitive adhesives, and in particular to a pressure-sensitive adhesive for bonding a polarizer in a display module to a liquid crystal panel and a display module. Background Art

[0002] With the popularization of electronic technology, liquid crystal displays have been widely used in all walks of life, and each display screen requires a polarizer of comparable area. The full name of polarizer is polarizing film. The imaging of liquid crystal displays must rely on polarized light. The front and rear polarizing films are tightly attached to the surface of the liquid crystal glass, forming a liquid crystal film with a total thickness of about 1mm. The bonding of the polarizing film and the liquid crystal glass requires bonding with pressure-sensitive adhesive. In order to adapt to the application in liquid crystal displays, the pressure-sensitive adhesive is required to have excellent adhesion, high adhesion, high transmittance, and excellent aging resistance (high temperature resistance, low temperature resistance, high temperature and high humidity resistance, cold and hot shock) performance. The main materials that make up the polarizer, such as the PVA (polyvinyl alcohol) layer, the upper and lower TAC (triacetyl cellulose) layers, the PSA (pressure-sensitive adhesive) layer, and the key material pressure-sensitive adhesive, are currently still imported. The imported pressure-sensitive adhesive is a two-component or three-component adhesive, and it is necessary to add curing agents and other additives before coating. The process is complicated, and there will be performance differences between batches in the preparation of each barrel of glue. After the pressure-sensitive adhesive is added with the curing agent, there will be a later cross-linking reaction, and a certain period of aging period is required. Even after the aging period, it does not mean that the cross-linking reaction has been completely completed. Therefore, during the aging resistance test, the cross-linking reaction causes a large change in the stress of the pressure-sensitive adhesive, resulting in shrinkage, warping, bubbles, and uneven display, which greatly increases product risks and production costs. Summary of the invention

[0003] In view of the above deficiencies in the prior art, an object of the present invention is to provide a pressure-sensitive adhesive for display and a preparation method thereof.

[0004] To achieve the above objectives, the technical solutions adopted are:

[0005] One of the purposes of the present invention is to provide a pressure-sensitive adhesive for display, comprising an acrylate copolymer and a solvent. The raw materials of the acrylate copolymer comprise, by weight, 100-150 parts of a soft monomer, 10-50 parts of a hard monomer, 1-10 parts of a cross-linking monomer, 1-10 parts of a macromonomer, 0.1-1 parts of an initiator, and 0-0.2 parts of an auxiliary agent.

[0006] Preferably, the weight average molecular weight of the acrylic ester copolymer is 2 million to 4 million, of which the molecular weight of 5 million or more accounts for ≥20%, and the polydispersity coefficient α is 1.8-3.2.

[0007] Preferably, the pressure-sensitive adhesive for display includes component A, component B, cross-linking monomer C, solvent C, initiator C, and auxiliary agent. The soft monomer includes soft monomer A and soft monomer B, the hard monomer includes hard monomer A and hard monomer B, the macromonomer includes macromonomer A and macromonomer B, the macromonomer includes macromonomer A and macromonomer B, the cross-linking monomer includes cross-linking monomer A, cross-linking monomer B and cross-linking monomer C, the initiator includes initiator A, initiator B and initiator C, the solvent includes solvent A, solvent B and solvent C, and the solvent includes solvent A, solvent B and solvent C. In parts by weight, the raw materials of component A include soft monomer A, hard monomer A, cross-linking monomer A, macromonomer A, initiator A, and solvent A, and the raw materials of component B include soft monomer B, hard monomer B, cross-linking monomer B, macromonomer B, initiator B, and solvent B.

[0008] More preferably, by weight, the raw materials of component A include 70-90 parts of soft monomer A, 5-25 parts of hard monomer A, 0.5-5 parts of crosslinking monomer A, 2-5 parts of macromonomer A, and 0.1-1 parts of initiator A, and the raw materials of component B include 20-40 parts of soft monomer B, 5-25 parts of hard monomer B, 0.5-5 parts of crosslinking monomer B, 1-10 parts of macromonomer B, and 0.1-1 parts of initiator B. Preferably, the soft monomer A and soft monomer B are each independently one or more of isooctyl (meth)acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, isononyl acrylate, tridecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, eicosyl (meth)acrylate, isooctadecyl (meth)acrylate, lauryl acrylate, isodecyl acrylate, and 2-ethylhexyl methacrylate, and n-butyl acrylate and lauryl acrylate are more preferred.

[0009] Preferably, the hard monomer A and the hard monomer B are each independently one or more of isobutyl methacrylate, tert-butyl methacrylate, methyl (meth)acrylate, isobornyl (meth)acrylate, benzyl acrylate, ethyl acrylate, and vinyl acetate, more preferably benzyl acrylate and vinyl acetate.

[0010] Preferably, the crosslinking monomer A, the crosslinking monomer B and the crosslinking monomer C are each independently one or more of acrylic acid, 2-hydroxyethyl acrylate, 4-hydroxybutyl acrylate, more preferably acrylic acid and 2-hydroxyethyl acrylate.

[0011] Preferably, the macromonomer A and the macromonomer B are each independently one or more of trimethylolpropane tri(meth)acrylate, tripentaerythritol octaacrylate, ethoxylated trimethylolpropane triacrylate, pentaerythritol tetraacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, ethoxyethoxyethyl acrylate, 2-propoxylated neopentyl glycol diacrylate, more preferably ethoxyethoxyethyl acrylate and 2-propoxylated neopentyl glycol diacrylate.

[0012] Preferably, initiator A, initiator B and initiator C are each independently one or more of azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptylnitrile, benzoyl peroxide, and tert-amyl peroxide 2-ethylhexanoate, more preferably azobisisobutyronitrile and tert-amyl peroxide 2-ethylhexanoate.

[0013] Preferably, the solvent A, solvent B and solvent C are each independently selected from one or more of methyl acetate, ethyl acetate, butyl acetate, acetone, butanone, toluene, xylene, methanol, ethanol, isopropanol, butanediol, propylene glycol methyl ether, dimethylformamide and cyclohexane, more preferably ethyl acetate and methyl acetate. The amount of the solvent A, solvent B and solvent C is not particularly limited, as long as each component can flow and distribute more evenly.

[0014] Preferably, the auxiliary agent includes at least one of a silane coupling agent, a leveling agent, an antioxidant, and an antistatic agent; the silane coupling agent is one or more of γ-aminopropyltriethoxysilane (KH550), γ-glycidyloxypropyltrimethoxysilane (KH560), γ-(methacryloyloxy)propyltrimethoxysilane (KH570), and vinyltrimethoxysilane (KH171), and more preferably the auxiliary agent is γ-glycidyloxypropyltrimethoxysilane (KH560).

[0015] In addition, the raw materials of the acrylate copolymer may also include oxygen-containing atom / benzene / heterocyclic structure monomers, and the oxygen-containing atom / benzene / heterocyclic structure monomers include but are not limited to: one or more of cyclohexyl acrylate, 3,3,5-trimethylcycloethyl acrylate, acryloylmorpholine, acrylamide, phenoxyethyl acrylate, methoxyethyl acrylate, and ethoxydiglycol acrylate.

[0016] The second object of the present invention is to provide a method for preparing the pressure-sensitive adhesive for display, comprising the following steps:

[0017] (1) Add soft monomer A, hard monomer A, crosslinking monomer A, macromonomer A and solvent A into reactor A and mix them evenly. Add initiator A into reactor A at 60-65° C. under nitrogen protection and keep the temperature for reaction for 1 hour to obtain component A;

[0018] (2) Add soft monomer B, hard monomer B, crosslinking monomer B, macromonomer B and solvent B into reactor B and mix them evenly. Add initiator B into reactor B at 60-65° C. under nitrogen protection and keep the temperature for reaction for 1 hour to obtain component B;

[0019] (3) Add component A, component B, and crosslinking monomer C into reactor C and mix them evenly. Under nitrogen protection, add initiator C into reactor C in batches at 75-80° C., and keep the temperature for reaction for 8-10 hours. After the reaction is completed, add auxiliary agent and solvent C, filter the material, and obtain the pressure-sensitive adhesive for display.

[0020] In the present invention, the pressure-sensitive adhesive is evenly coated on the release layer of the 36um PET release film using a scraper, and dried in an oven at 85-100°C, with the adhesive layer having a thickness of 15-25μm, preferably 20um. After drying, the polarizer is attached without the need for a curing process.

[0021] Compared with the prior art, the beneficial effects of the present invention are as follows: the preparation method of the pressure-sensitive adhesive of the present invention, by respectively introducing macromolecular groups into component A and component B in the early stage, reacting them into prepolymers, and then continuing to mix and cross-link the two prepolymers, greatly improves the weight average molecular weight Mw level of the pressure-sensitive adhesive, increases the molecular weight ratio by 5 million, and controls the polydispersity coefficient α of the molecular weight distribution within 1.8-3.2, thereby improving the stability of the product, reaching and exceeding the effect of the existing two-component or three-component;

[0022] The pressure-sensitive adhesive of the present invention is a single component, can be used directly, and has a simple and controllable process; there is no need to add a curing agent later, thereby avoiding the risk of aging failure caused by batch differences of the curing agent and the post-crosslinking process. By using a macromolecular monomer and a reasonable preparation method, the molecular weight of the pressure-sensitive adhesive is greatly improved and the molecular weight distribution is controlled within a narrow range. The obtained pressure-sensitive adhesive has excellent adhesion, high adhesion, high light transmittance and other properties, and has excellent aging resistance (high temperature resistance, low temperature resistance, high temperature and high humidity resistance, cold and hot shock) performance, and meets the process performance of anti-warping, cutting performance, and rework performance, and meets the use requirements. DETAILED DESCRIPTION

[0023] The present invention is described below in conjunction with examples, which are only used to explain the present invention and are not used to limit the scope of the present invention.

[0024] 1. Preparation of pressure-sensitive adhesive

[0025] The preparation of the acrylic ester copolymer of the pressure-sensitive adhesive is mainly based on solvent polymerization, which includes free radical polymerization, addition, esterification, etc. The raw material formula of the acrylic ester copolymer is shown in Table 1, which does not include the solvent content.

[0026] The raw materials of the acrylic ester copolymer include soft monomers, hard monomers, cross-linking monomers, macromonomers, etc. The values ​​in Table 1 are parts by weight.

[0027] Table 1. Raw material formula of acrylic copolymer

[0028]

[0029]

[0030] Among them, BA is n-butyl acrylate; BZA is benzyl acrylate; HEA is 2-hydroxyethyl acrylate; EOEOEA is ethoxyethoxyethyl acrylate; LA is lauryl acrylate; VAC is vinyl acetate; PO-NPGDA is 2-propoxy neopentyl glycol diacrylate; AA is acrylic acid; KH560 is γ-glycidyloxypropyltrimethoxysilane; AIBN isobutylene glycol nitrile; TAPO is tert-amyl peroxy 2-ethylhexanoate.

[0031] The preparation process of Example 1 is as follows:

[0032] (1) Using a free radical thermal polymerization method, soft monomer A, hard monomer A, crosslinking monomer A, macromonomer A and solvent A are added to reactor A and mixed evenly. Under nitrogen protection, 0.1 parts of AIBN are added to reactor A at 60-65° C. to initiate the reaction. The reaction is kept warm for 1 hour to obtain component A;

[0033] (2) using a free radical thermal polymerization method, adding soft monomer B, hard monomer B, cross-linking monomer B, macromonomer B and solvent B into reactor B and mixing them evenly, adding 0.1 parts of AIBN into reactor B at 60-65° C. under nitrogen protection to initiate the reaction, and keeping the temperature for 1 hour to obtain component B;

[0034] (3) Component A, component B, and crosslinking monomer C are added to reactor C and mixed evenly. Under nitrogen protection, 0.3 parts of TAPO are added to reactor C in batches at 75-80° C. for initiation. The reaction is kept warm for 8-10 hours. After the reaction is completed, KH560 and solvent C are added, and the material is filtered to obtain the pressure-sensitive adhesive for display.

[0035] The preparation of Examples 1 to 8 was carried out according to the proportions in Table 1, and the preparation process was the same as that of Example 1.

[0036] Comparative Example 1

[0037] The preparation processes of Comparative Example 1 and Example 5 are the same, and the difference in the formula is that component A does not contain the macromonomer EOEOEA.

[0038] Comparative Example 2

[0039] The preparation processes of Comparative Example 2 and Example 5 are the same, and the difference in the formula is that component B does not contain the macromonomer PO-NPGDA.

[0040] Comparative Example 3

[0041] The ratio of Comparative Example 3 is the same as that of Example 5, except that the prepolymer of component A and component B is not synthesized separately in the preliminary stage of Comparative Example 3. The preparation process of Comparative Example 3 is as follows: using a free radical thermal polymerization method, all soft monomers, hard monomers, cross-linking monomers, macromolecular monomers and solvents in the ratio are fully mixed, nitrogen is introduced and heated to 60-65°C, and then 0.2 parts of AIBN are used for initiation and the reaction is carried out for 1 hour; after heating to 75-80°C, 0.3 parts of TAPO are added in batches into the reaction container and reacted for 8-10 hours. After the reaction is completed, KH560 and the remaining solvent are added, and the material is cooled and discharged.

[0042] 2. Coating of pressure-sensitive adhesive

[0043] The pressure-sensitive adhesive is evenly coated on the 36um PET release film using a scraper, and dried in an oven at 85-100°C, with the adhesive layer thickness of 20um±2um. After drying, the polarizer is attached to obtain a sample without the need for a curing process.

[0044] test

[0045] The pressure-sensitive adhesives obtained in Examples 1 to 8 and Comparative Examples 1 to 3 were subjected to the following tests:

[0046] (1) Molecular weight and molecular weight distribution: The weight average molecular weight (Mw), the proportion of molecular weight above 5 million, and the molecular weight distribution polydispersity coefficient α were measured by gel permeation chromatography (GPC).

[0047] (2) Adhesion performance: The sample was cut into 25 mm width, attached to the glass, and the 180° peel strength was tested.

[0048] (3) Holding force: Cut the sample into 25 mm wide pieces and stick them on the surface of the steel plate with a sticking area of ​​25 mm × 25 mm. Hang a weight of 1000 g, set the temperature to 85°C, and test the displacement distance for 10,000 minutes. If the drop time is less than 10,000 minutes, record the drop time.

[0049] (4) Light transmittance: The light transmittance was tested at normal state and after 72 hours at 85°C and 85%.

[0050] (5) Anti-warping: Cut the sample into 210×297 mm, stick it on the test glass with a thickness of 0.5 mm, place it at 60 degrees Celsius for 72 hours, observe the warping and record the warping distance.

[0051] (6) Light leakage prevention: Two samples were attached to the two sides of 0.5 mm thick glass in a manner that the polarizers were orthogonal to each other (at an angle of 90 degrees). The orthogonal transmittance was tested using a UV spectrophotometer, with the sample at the initial stage of aging being 0%. The orthogonal transmittance was tested again at 85°C and 85% for 168 hours.

[0052] (7) Aging resistance: A 210×297 mm sample was attached to one side of a 0.5 mm thick glass and placed in the following aging environments: high temperature 85°C; wet heat 60°C / 90% RH; freezing -40°C for 1000 hours each; hot and cold shock -40 to +85°C for 200 cycles. The bonding flatness, blistering, warping, and peeling phenomena were observed.

[0053] (8) Cutting performance: Use a paper cutter to cut a 210×297 mm sample into approximately four equal pieces along the center of the sample. Cut 10 pieces in a row and observe whether there is glue extrusion, glue damage, glue shortage, etc.

[0054] (9) Reworkability: Cut the sample into 25 mm width and laminate it to glass. After leaving it at room temperature for 30 days, remove the sample and check whether there is any residual glue on the glass.

[0055] The results of the above tests are shown in Table 2.

[0056] Table 2. Test results of pressure-sensitive adhesives of Examples 1 to 8 and Comparative Examples 1 to 3

[0057]

[0058]

[0059]

[0060] It can be seen from the test results in Table 2 that Example 5 has better comprehensive performance and can be used as the best example of the present invention. It can be seen from the results shown in Table 2 that the pressure-sensitive adhesive used in the present invention meets the requirements.

[0061] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A pressure-sensitive adhesive for display, characterized in that: The invention comprises an acrylate copolymer and a solvent. The raw materials of the acrylate copolymer comprise, by weight, 100-150 parts of a soft monomer, 10-50 parts of a hard monomer, 1-10 parts of a cross-linking monomer, 1-10 parts of a macromolecular monomer, 0.1-1 parts of an initiator and 0-0.2 parts of an auxiliary agent.

2. The pressure-sensitive adhesive for display according to claim 1, characterized in that: The weight average molecular weight of the acrylic ester copolymer is 2 million to 4 million, of which the molecular weight above 5 million accounts for ≥20%, and the polydispersity coefficient α is 1.8-3.

2.

3. The pressure-sensitive adhesive for display according to claim 1, characterized in that: The invention comprises component A, component B, crosslinking monomer C, solvent C, initiator C and auxiliary agent, wherein the soft monomer comprises soft monomer A and soft monomer B, the hard monomer comprises hard monomer A and hard monomer B, the macromonomer comprises macromonomer A and macromonomer B, the macromonomer comprises macromonomer A and macromonomer B, the crosslinking monomer comprises crosslinking monomer A, crosslinking monomer B and crosslinking monomer C, the initiator comprises initiator A, initiator B and initiator C, the solvent comprises solvent A, solvent B and solvent C, and the raw materials of component A comprise soft monomer A, hard monomer A, crosslinking monomer A, macromonomer A, initiator A and solvent A, and the raw materials of component B comprise soft monomer B, hard monomer B, crosslinking monomer B, macromonomer B, initiator B and solvent B.

4. The pressure-sensitive adhesive for display according to claim 3, characterized in that: The soft monomer A and the soft monomer B are each independently one or more of isooctyl (meth)acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, isononyl acrylate, tridecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, eicosyl (meth)acrylate, isooctyl (meth)acrylate, lauryl acrylate, isodecyl acrylate, and 2-ethylhexyl methacrylate.

5. The pressure-sensitive adhesive for display according to claim 3, characterized in that: The hard monomer A and the hard monomer B are independently selected from one or more of isobutyl methacrylate, tert-butyl methacrylate, methyl (meth)acrylate, isobornyl (meth)acrylate, benzyl acrylate, ethyl acrylate and vinyl acetate.

6. The pressure-sensitive adhesive for display according to claim 3, characterized in that: The cross-linking monomer A, the cross-linking monomer B and the cross-linking monomer C are each independently one or more of acrylic acid, 2-hydroxyethyl acrylate and 4-hydroxybutyl acrylate.

7. The pressure-sensitive adhesive for display according to claim 3, characterized in that: The macromonomer A and macromonomer B are each independently one or more of trimethylolpropane tri(meth)acrylate, tripentaerythritol octaacrylate, ethoxylated trimethylolpropane triacrylate, pentaerythritol tetraacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, ethoxyethoxyethyl acrylate, and 2-propoxylated neopentyl glycol diacrylate.

8. The pressure-sensitive adhesive for display according to claim 3, characterized in that: Initiator A, initiator B and initiator C are each independently one or more of azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptanenitrile, benzoyl peroxide and tert-amyl peroxy-2-ethylhexanoate.

9. The pressure-sensitive adhesive for display according to claim 3, characterized in that: The solvent A, solvent B and solvent C are each independently one or more of methyl acetate, ethyl acetate, butyl acetate, acetone, butanone, toluene, xylene, methanol, ethanol, isopropanol, butanediol, propylene glycol methyl ether, dimethylformamide, and cyclohexane, and the auxiliary agent includes at least one of a silane coupling agent, a leveling agent, an antioxidant, and an antistatic agent.

10. A method for preparing the pressure-sensitive adhesive for display according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) Add soft monomer A, hard monomer A, crosslinking monomer A, macromonomer A and solvent A into reactor A and mix them evenly. Add initiator A into reactor A at 60-65° C. under nitrogen protection and keep the temperature for reaction for 1 hour to obtain component A; (2) Add soft monomer B, hard monomer B, crosslinking monomer B, macromonomer B and solvent B into reactor B and mix them evenly. Add initiator B into reactor B at 60-65° C. under nitrogen protection and keep the temperature for reaction for 1 hour to obtain component B; (3) Add component A, component B, and crosslinking monomer C into reactor C and mix them evenly. Under nitrogen protection, add initiator C into reactor C in batches at 75-80° C., and keep the temperature for reaction for 8-10 hours. After the reaction is completed, add auxiliary agent and solvent C, filter the material, and obtain the pressure-sensitive adhesive for display.